Comparative Analysis of Financial Performance (CR, DER, ROA) Before and After Merger Study on Companies Listed on The IDX - Herdiawan, Refa Nabella; Moh. Nadhir Mua’mmar; Vemy Suci Asih; Dadang Husen Sobana (Indonesian Journal of Economics and Management, 2025)
Mergers and acquisitions (M&A) are key growth strategies for companies listed on the Indonesia Stock Exchange (IDX), expected to enhance financial performance through efficiency-based synergies. However, empirical findings often vary. This study aims to compare the financial performance of IDX-listed companies before and after mergers, measured by the Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA). Using a quantitative comparative approach, the sample includes six companies that merged between 2002 and 2021, with data derived from IDX annual reports. Analysis methods include descriptive statistics, the Kolmogorov-Smirnov normality test, and the Paired Samples T-Test using SPSS. Results indicate no significant differences in CR (p=0.344), DER (p=0.079), or ROA (p=0.283) before and after mergers. Despite slight improvements in DER and ROA, changes are not statistically significant, suggesting that financial benefits from M&A may require longer-term observation or be influenced by post-merger integration challenges.